Teaching English rhythm - Gilbert, Judy B. (2017)
Rhythm is basic to our home identity. The first part of language that we all learned as infants (starting even before birth) is the rhythm of our mother’s language (Werker & Gervain, 2013). By the time we have reached the age of one, the rhythm of the mother tongue is deeply familiar to us, and we unconsciously tend to apply it to any L2 that we are learning. That is why it is highly important that students of English be made consciously aware of how rhythm is at the centre of how spoken English works. Students and teachers need to be encouraged to think not of subtracting an accent, but of adding a new one for use when it would be helpful. This is known as code-switching. Students should be helped to view English pronunciation like a jacket that you can choose to put on or take off, depending on who you are speaking with. This is practical.